The narcissistic masculinity of Travis Bickle : American "Reality" in Martin Scorsese's Taxi Driver - Pauw, Waldemar (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (English))—University of Stellenbosch, 2006.